Mitochondria: one of the vital hubs for molecular hydrogen’s biological functions - Zhang, Xiaoyue; Xie, Fei; Ma, Shiwen; Ma, Chen; Jiang, Xue; Yi, Yang; Song, Yifei; Liu, Mengyu; Zhao, Pengxiang; Ma, Xuemei (Frontiers in Cell and Developmental Biology, 2023)
As a novel antioxidant, a growing body of studies has documented the diverse biological effects of molecular hydrogen (H2) in a wide range of organisms, spanning animals, plants, and microorganisms. Although several possible mechanisms have been proposed, they cannot fully explain the extensive biological effects of H2. Mitochondria, known for ATP production, also play crucial roles in diverse cellular functions, including Ca 2+ signaling, regulation of reactive oxygen species (ROS) generation, apoptosis, proliferation, and lipid transport, while their dysfunction is implicated in a broad spectrum of diseases, including cardiovascular disorders, neurodegenerative conditions, metabolic disorders, and cancer. This review aims to (1) summarize the experimental evidence on the impact of H2 on mitochondrial function; (2) provide an overview of the mitochondrial pathways underlying the biological effects of H2, and (3) discuss H2 metabolism in eukaryotic organisms and its relationship with mitochondria. Moreover, based on previous findings, this review proposes that H2 may regulate mitochondrial quality control through diverse pathways in response to varying degrees of mitochondrial damage. By combining the existing research evidence with an evolutionary perspective, this review emphasizes the potential hydrogenase activity in mitochondria of higher plants and animals. Finally, this review also addresses potential issues in the current mechanistic study and offers insights into future research directions, aiming to provide a reference for future studies on the mechanisms underlying the action of H2.